Major Depression and Survival in People With Cancer. Issue 5 (June 2021) - Walker, Jane; Mulick, Amy; Magill, Nicholas; Symeonides, Stefan; Gourley, Charlie; Burke, Katy; Belot, Aurelien; Quartagno, Matteo; van Niekerk, Maike; Toynbee, Mark; Frost, Chris; Sharpe, Michael
ABSTRACT: Objective: The question of whether depression is associated with worse survival in people with cancer remains unanswered because of methodological criticism of the published research on the topic. We aimed to study the association in a large methodologically robust study. Methods: We analyzed data on 20, 582 patients with breast, colorectal, gynecological, lung, and prostate cancers who had attended cancer outpatient clinics in Scotland, United Kingdom. Patients had completed two-stage screening for major depression as part of their cancer care. These data on depression status were linked to demographic, cancer, and subsequent mortality data from national databases. We estimated the association of major depression with survival for each cancer using Cox regression. We adjusted for potential confounders and interactions between potentially time-varying confounders and the interval between cancer diagnosis and depression screening, and used multiple imputation for missing depression and confounder data. We pooled the cancer-specific results using fixed-effects meta-analysis. Results: Major depression was associated with worse survival for all cancers, with similar adjusted hazard ratios (HRs): breast cancer (HR = 1.42, 95% confidence interval [CI] = 1.15–1.75), colorectal cancer (HR = 1.47, 95% CI = 1.11–1.94), gynecological cancer (HR = 1.36, 95% CI = 1.08–1.71), lung cancer (HR = 1.39, 95% CI = 1.24–1.56), and prostate cancer (HR = 1.76, 95% CI = 1.08–2.85). The pooled HR was 1.41 (95% CI = 1.29–1.54, p < .001, I 2 = 0%). These findings were not materially different when we only considered the deaths (90%) that were attributed to cancer. Conclusions: Major depression is associated with worse survival in patients with common cancers. The mechanisms of this association and the clinical implications require further study. Abstract : Supplemental digital content is available in the text.